Validation of the UK myeloma research alliance risk profile, a new clinical prediction model for outcome in patients with newly diagnosed multiple myeloma not eligible for autologous stem cell transplantation; a population‐based study from the Danish national multiple myeloma registry. (9th June 2020) - Redder, Louise; Klausen, Tobias W.; Vangsted, Annette Juul; Gregersen, Henrik; Andersen, Niels F.; Pedersen, Robert S.; Szabo, Agoston G.; Frederiksen, Mikael; Frølund, Ulf C.; Helleberg, Carsten; Nielsen, Lene Kongsgaard; Pedersen, Per T.; et al.
Summary: In 2019 the UK Myeloma Research Alliance introduced the Myeloma Risk Profile (MRP) for prediction of outcome in patients with newly diagnosed multiple myeloma (MM), ineligible for autologous stem cell transplantation. To validate the MRP in a population‐based setting we performed a study of the entire cohort of transplant ineligible MM patients above 65 years in the Danish National MM Registry. Our data confirmed the value of the MRP. In a cohort of 1, 377 patients, the MRP score separated patients into three distinct risk‐groups with an observed hazard ratio of 2.91 for early death in high‐risk versus low‐risk patients.